Halogen‐Bonded BODIPY Frameworks with Tunable Optical Features. Issue 5 (23rd December 2020) - Özcan, Emrah; Dedeoglu, Burcu; Chumakov, Yuri; Gürek, Ayşe Gül; Zorlu, Yunus; Çoşut, Bünyemin; Menaf Ayhan, Mehmet
Abstract: The ability to tune the optical features of BODIPY materials in the solid state is essential for their photorelated application and requires efficient control of the crystal packing. In this study, such control of BODIPY supramolecular assemblies was achieved by deliberate design and synthesis of a BODIPY containing a strong halogen‐bond (XB) acceptor (−NO2 ) and donor (I, Br) to mediate XB interactions. The di‐halogenated structures formed isostructural mono‐coordinate motif B3, B4 (1D tubular structure) and symmetric bifurcated motif B4‐II (1D zigzag chains structure) through N−O⋅⋅⋅I, Br XB interactions. These XB interactions promote singlet‐to‐triplet intersystem crossing and triplet‐to‐singlet reverse intersystem crossing due to partial delocalization of oxygen electrons onto Br and I, which leads to unexpected fluorescence enhancement of B4‐II . Finally, the indirect optical band gaps of B3, B4 and B4‐II were amenable to tuning in the range of 1.85–2.50  eV by XB‐driven crystal packings. Abstract : The importance of packing correctly : Here, we present the targeted design and synthesis of halogen bonding (XB)‐mediated BODIPY supramolecular frameworks. The optical features of these frameworks, including the fluorescence intensity and optical band gap, were successfully tuned by XB‐driven crystal packing.